Analysis Of The Impact Of Tax Reform On Income Tax (PPH) 21 Revenue In Indonesia - Wulidatul Imro'ah; Kika Andira; M. Zahid Zakhrafi; Sunairah; Yovita Kusuma (International Journal of Sociology of Religion, 2023)
This research aims to analyze the impact of tax reform on Income Tax (PPH) 21 revenues in Indonesia. Tax reform was carried out by the government to increase efficiency and fairness in the tax system. The main focus of this research is identifying tax policy changes that have been implemented and analyzing how these changes affect PPH Article 21 revenue. This research uses a qualitative approach with descriptive methods, while the type of research uses literature study research to analyze tax policy, as well as the impact of tax reform on revenue. PPH Article 21. It is hoped that the results of this research will provide a better understanding of the effectiveness of tax reform in increasing income tax revenues from high-income employees.